Pengembangan Metode Kooperatif Tipe Group Investigation Pada Ekstrakurikuler Drumband Esteem Voice SMKN 1 Nganjuk - Fahim Putri Oktaviana Fahim Putri Oktaviana; Trisakti (Universitas Negeri Surabaya, 2025)
Drumband is a collective activity involving many participants. There is a division of instruments based on their roles and functions within the drumband. The material delivered to each instrument group differs according to its specific function. The varying abilities of drumband members, combined with the complex harmonization and teamwork required in drumband performances, present unique challenges. This study aims to describe the implementation of the Group Investigation type of cooperative learning method in the extracurricular activities of the Esteem Voice Drumband. The research method used in this study is descriptive qualitative research, with data collection techniques including interviews with coaches and students, passive participatory observation during practice sessions, and documentation as supporting data. The data analysis techniques consist of data reduction, data presentation, and data verification. The implementation of the Group Investigation cooperative learning method in the Esteem Voice Drumband extracurricular activities includes six stages: (1) topic selection and student organization, (2) planning of learning procedures, (3) implementation of the learning process, (4) analysis and synthesis of the material, (5) presentation of the final results, and (6) evaluation.